2013
DOI: 10.1088/2043-6262/4/1/015009
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet printing technology and conductive inks synthesis for microfabrication techniques

Abstract: Inkjet printing is an advanced technique which reliably reproduces text, images and photos on paper and some other substrates by desktop printers and is now used in the field of materials deposition. This interest in maskless materials deposition is coupled with the development of microfabrication techniques for the realization of circuits or patterns on flexible substrates for which printing techniques are of primary interest. This paper is a review of some results obtained in inkjet printing technology to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…The print process conditions were set as follows: the cartridge temperature was 35 °C and the substrate temperature was 45 °C in order to achieve a good sintering of a drop on the substrate. After the printing process the antenna was dried in a vacuum oven at 120 °C for 20 minutes in order to sinter the nanoparticles and create a compact layer [10][11][12][13][14][15][16]. 2.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The print process conditions were set as follows: the cartridge temperature was 35 °C and the substrate temperature was 45 °C in order to achieve a good sintering of a drop on the substrate. After the printing process the antenna was dried in a vacuum oven at 120 °C for 20 minutes in order to sinter the nanoparticles and create a compact layer [10][11][12][13][14][15][16]. 2.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The literature pertaining to inkjet depositions of TiO 2 has focused on depositions of TiO 2 suspensions for the formation of TiO 2 layers with a uniform density [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. No consistent TiO 2 suspension formulations have been reported for inkjet printing with the exception of Deionized (DI) water as a primary solvent.…”
Section: Deposition Methods For Tiomentioning
confidence: 99%
“…Several major design variations exist for inkjet printers, variations that have been developed in response to the many diverse applications that printers have been tailored to over the past several decades [16]. There are two primary printer categorizations, continuous and Drop on demand (DOD), that are often used to differentiate commercial and industrial printing from consumer printing.…”
Section: C2 Inkjet Printingmentioning
confidence: 99%
“…3,4 CuNPs are also promising candidate materials for replacing expensive noble metals such as Au, Pt, and Ag in microscale electronic devices. As such, in the last few decades, many techniques have been developed for the synthesis of CuNPs; these include chemical reduction, [5][6][7][8] microwave heating, 9 vacuum vapor deposition, 10 laser blation, 11 microemulsion methods, [12][13][14] radiation methods, 15 and sono-chemical reduction. 16 However, controlling the characteristics (e.g., size, shape, surface, dispersion, and agglomeration) of the CuNPs is difficult owing to the multiple complex mechanisms stemming from capping agents, chemical decomposition, and susceptible oxidation of CuNPs.…”
Section: Introductionmentioning
confidence: 99%
“…17 Similarly, Dang et al showed that CuNPs could be synthesized without inert gas protection, under copper sulfate and sodium borohydride in water. 8 As for CuNP applications, Lee et al used metallic copper traces as inkjet-printed electronics in a polyimide substrate after the sintering process. 4 In addition, Ramgir et al introduced an ammonia gas sensor based on nanocomposites composed of copper nanoparticles and polyaniline.…”
Section: Introductionmentioning
confidence: 99%